Application of TERRA/MODIS images, TM images and weather data to assess the effect of cold damage on rice yield - Yingbin, He; Uchida, Satoshi; Huajun, Tang; Youqi, Chen; Jia, Liu (International Journal of Agricultural and Biological Engineering, 2010)
Data assimilation is extensively applied in agricultural remote sensing application. However, integration of multi-temporal and high spatial resolution images with crop growth model to evaluate the effect of cold damage on paddy rice was still lacking. In this paper, authors applied data assimilation combining LANDSAT/TM, a series of terra MODIS images with SIMRIW model to detect how cold damage affected paddy rice yield per unit in the Wuchang county, Heilongjiang province for the year 2006. In the study, MODIS images selected corresponding to a series of the key rice growth phases were utilized to retrieve daily LAI values that were needed in the SIMRIW model. Meanwhile, TM was applied to accurately extract paddy rice sown areas. The study results showed that the yield per unit was 10,628.5840 kg/ha under cold damage condition, which was little less than 10,768.3210 kg/ha under optimal condition. Moreover, the ratio of the calculated yield per value under cold damage condition to the actual value of paddy rice yield per unit was 0.56. The result was better than that acquired in USA and Japan. The results of this study expected to provide suggestions to policy-makers and reference to related research. Keywords: data assimilation, MODIS, TM, cold damage, rice yield per unit, NDVI, LAIDOI: 10.3965/j.issn.1934-6344.2010.02.031-038 Citation: He Yingbin, Satoshi Uchida, Tang Huajun, Chen Youqi, Liu Jia. Application of TERRA/MODIS images, TM images and weather data to assess the effect of cold damage on rice yield. Int J Agric & Biol Eng, 2010; 3(2): 31<span style="font-size: 9.5pt; font-family: